Rare earths - What is the answer to China's monopoly? - Schwartz M. (The Institute of Materials, Minerals and Mining, 2015)
The current status of the heavy and light rare-earth elements outside China is reviewed. New suppliers of the light rare-earth elements are Lynas (Australia/Malaysia) and Molycorp (USA), which are anticipated to process 11 000 and up to 10 000 t/y, respectively, and the most advanced heavy rare-earth elements project is Avalon's Nechalacho project at Thor Lake, Northwest Territories, Canada. U3O8 Corp has potential rare-earth elements production, e.g. ytrrium and neodymium, from its Berlin deposit in Colombia and Namibia Rare Earth's Lofdal project (Area 4) has potential to produce an average of 1 500 t/y of separated rare-earth oxides. With regard to the three historical producers, India has some small-scale production, Brazil has been a small-volume producer and has potential for new heavy rare-earth elements production, while South Africa has no current production